2016
DOI: 10.1002/2016wr018926
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Belmont et al. on “Climate and agricultural land use change impacts on streamflow in the upper midwestern United States”

Abstract: The reply addresses concerns raised by Belmont et al. (2016) on Gupta et al. (2015) through additional analysis of streamflow versus precipitation relationships for the Whetstone and the Redwood Rivers and with data on available soil moisture in prechange and postchange periods in the Cottonwood River watershed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The overall influence of agricultural land cover and of changing agricultural practices on streamflows across the Midwest has led to heated debates in recent years [20,[69][70][71][72][73][74][75][76]. In the Upper Mississippi River Basin, LULC has a clear signature on streamflow [77].…”
Section: Agriculturementioning
confidence: 99%
“…The overall influence of agricultural land cover and of changing agricultural practices on streamflows across the Midwest has led to heated debates in recent years [20,[69][70][71][72][73][74][75][76]. In the Upper Mississippi River Basin, LULC has a clear signature on streamflow [77].…”
Section: Agriculturementioning
confidence: 99%
“…In their comment, Foufoula‐Georgiou et al . [] state that “Progressive conversion of wetlands to cultivated land and replacement of small grains with corn and soybeans …… are altering evapotranspiration and water cycle dynamic.” We believe that presence of certain crops or areas of crops as proof that evapotranspiration or water cycle has changed is not a solid basis for a scientific conclusion [See Gupta et al ., , ]. On the other hand, Gupta et al .…”
Section: Selected Annual Precipitation and Streamflow (Gage = 0531650mentioning
confidence: 51%
“…are altering evapotranspiration and water cycle dynamic.'' We believe that presence of certain crops or areas of crops as proof that evapotranspiration or water cycle has changed is not a solid basis for a scientific conclusion [See Gupta et al, 2016bGupta et al, , 2016c. On the other hand, Gupta et al [2015] showed that ET of corn and soybeans is much greater than those of small grains and other crops in the prechange period.…”
mentioning
confidence: 99%
“…In further analysis of bi-monthly streamflows, Foufoula-Georgiou et al (2015) concluded that increased streamflow from May-June was primarily due to land use changes (adoption of soybean and tile drainage) because there was not much difference in May-June precipitation distributions before and after adoption of the above LULC changes. Similar to their daily comparisons between 2002and 1971, Foufoula-Georgiou et al (2015 also overlooked the increased November-December precipitation in recent years and the role it played in increased stored soil water in spring and in turn on May-June streamflow in the postchange period (Gupta et al, 2016d.…”
mentioning
confidence: 75%
“…The LULC changes include increased tile drainage, cultivation of prairies, and adoption of soybean (Glycine max) in modern-day cropping systems. However, a recent analysis of streamflow records from 29 HUC 8 (Hydrologic Unit Code 008) watersheds in Iowa and Minnesota showed that climate change (increased precipitation) rather than LULC change was the major driver of increased annual streamflow in the upper Midwestern U.S. (Gupta et al, 2015(Gupta et al, , 2016a(Gupta et al, , 2016b(Gupta et al, , 2016c(Gupta et al, , 2016d. The analysis was done through hierarchical regression analysis of annual streamflow as a function of annual precipitation for the periods prior to 1975 (pre-change period) and after 1976 (post-change period).…”
mentioning
confidence: 99%